An innovation in stem cell harvesting: Heparin use - Gul, Hacer Gozde; Erkurt, Mehmet Ali; Sarici, Ahmet; Kuku, Irfan; Kaya, Emin; Berber, Ilhami; Ozgul, Mustafa (Pergamon-Elsevier Science Ltd, 2021)
Background and Objectives: Stem cell transplantation is a growing treatment strategy for most malignant and nonmalignant hematological diseases. Plerixafor and granulocyte colony stimulating factor (G-CSF) are usually used in mobilization regimens to increase the CD34+ cell count in the harvest. Heparin is a sulphated glycosaminoglycated polymer with 12-15 kDa mass. Heparin inhibits the CXCR4/SDF1 axis, as does plerixafor. In this study, our aim was to investigate the effect of using heparin on stem cell mobilization and harvesting. Materials and Methods: We administered 5000 units of unfractioned heparin intravenously in 150 mL (mL) of isotonic sodium chloride solution, 15 min before the stem cell harvesting procedure to 141 patients who underwent bone marrow transplantation between the years of 2018 and 2019 at our Stem Cell Transplantation Unit. Thirty patients were included as a control group, and they were not given heparin. The study population included patients with multiple myeloma and lymphoma equally in each group. Results: In all patients hematopoeitic stem cells were successfully harvested in a single cycle of apheresis. In multiple myeloma patients who received heparin, the mean collected CD34+ cell number was 8 x 10(6)/kg, and the mean CD34+ cell number yield was 12,555/mu l. In the control group, the mean collected CD34+ cell number was 4,2 x 10(6)/kg, and mean CD34+ cell number in yield was 492/mu l. In lymphoma patients who received heparin, the mean collected CD34+ cell number was 6,8 x 10(6)/kg, and the mean CD34+ cell number was 1421/ mu l. In the control group the mean collected CD34+ cell number was 4,3 x 10(6)/kg, and the mean CD34+ cell number was 358/mu l. The effect of heparin on the collected stem cell number in both myeloma and lymphoma patients was statistically significant (p < 0.01) Conclusions: Our results have shown that heparin increases harvested stem cell numbers significantly. Heparin may be a promising agent for stem cell harvesting.
Keywords: Stem cell harvesting; Mobilization; Heparin; G-CSF; Plerixafor